Development of a Sequential Injection Analysis System for the Determination of Saccharin - Budi Wibowotomo; Jong-Bang Eun; Jong Il Rhee (Sensors, 2017)
Saccharin is a powerfully sweet nonnutritive sweetener that has been approved for food-processing applications within the range of 100–1200 mg/kg. A simple, rapid, and cost-effective sequential injection analysis (SIA) technique was developed to determine the saccharin level. This method is based on the reaction of saccharin with p-chloranil in an ethanol medium with a hydrogen peroxide (H2O2) acceleration, and the resultant violet-red compound was detected using a UV-Vis spectrophotometer at λmax = 420 nm. To ascertain the optimal conditions for the SIA system, several parameters were investigated, including buffer flow rate and volume, p-chloranil concentration, and reactant volumes (saccharin, p-chloranil, and H2O2). The optimum setup of the SIA system was achieved with a buffer flow rate, buffer volume, and draw-up time of 1.2 mL/min, 2900 µL, and ~145 s, respectively. The optimal p-chloranil concentration is 30 mM, and the best reactant volumes, presented in an ordered sequence, are as follows: 30 µL of H2O2, 450 µL of saccharin, and 150 µL of p-chloranil. The optimized SIA configuration produced a good linear calibration curve with a correlation coefficient (R2 = 0.9812) in the concentration range of 20–140 mg/L and with a detection limit of 19.69 mg/L. Analytical applications in different food categories also showed acceptable recovery values in the range of 93.1–111.5%. This simple and rapid SIA system offers great feasibility for the saccharin quality control in food-product processing.